Over a million students use our free study notes to help them with their homework
=(x^4)/4+(4x^3)/3 + 3x + c
First point out that it makes sense to solve this system of equations using the substitution method because one of the variables can easily be isolated without multiplication or division.(Step 1:) Label t...
Jasmine's age + 9 = Ella's age: therefore, J + 9 = E4 x Ella's age = Katherine's age: therefore, 4E = KThe sum of Jasmine's, Ella's and Katherine's ages = 72: therefore, J + E + K = 72take J + E + K = 72 ...
(3c+b)/2 = c + a To make c the subject of this equation, we first must get all the c variables together on one side of the equation.To do this, first we shall multiply both sides by 2 to remove it from th...
We can see that x=y-1 and therefore can sub this in our first equation, to give us 3(y-1)+2y=22. If we expand the brackets we than have 3y-3+2y=22 which can be tidied up to give 5y-3=22. If we add 3 to bo...
←
554
555
556
557
558
→
Internet Safety
Payment Security
Cyber
Essentials